Electronic Library: Read in successful models - Abu Hikma, Halima Mohammed (Journal of Educational and Psychological Sciences, 2019)
This study has been prepared to deal with the groups of electronic libraries, their creations, their developments, their churacties, their advantages as well as the basic functions to establish this type of libraries which are also opened to internet and the future trends. this research has got same of the results and recommendations.
Keywords: electronic library; internet; computer; reading